POETICS OF FARIDA AFRUZ'S POETRY (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article analyzes the genre and stylistic features of the work of Farida Afroz, one of the prominent representatives of modern Uzbek poetry. In the poetess's poetry, the priority of short lyrical genres, minimalist expression, poetic silence, and the system of symbolic images are scientifically and theoretically illuminated. In the process of analysis, scientific sources on the theory of modern Uzbek poetry are relied upon.